2022
DOI: 10.1002/ett.4476
|View full text |Cite
|
Sign up to set email alerts
|

A new method of hybrid optimization of small cell range development and density for energy efficient ultra‐dense networks

Abstract: Ultra-dense networks (UDNs) which comprise of small and macro cells, are considered the principal solution for increasing demands of data. However, making energy efficient networks will be a challenge for researchers. In this article, a hybrid optimization technique is proposed to enhance the energy efficiency (EE) of the UDNs, considering the user correlation and hybrid optimization of the density and transmitting power of the small-cell-base-station (SBS). More precisely, the problem framed is a problem of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…They also indicated that connecting photonics well-defined radio with machine learning (ML) will be a major development of artificial intelligencein 6G. The 6G technologies, scenarios, and system architecture were also described [6].…”
Section: Related Workmentioning
confidence: 99%
“…They also indicated that connecting photonics well-defined radio with machine learning (ML) will be a major development of artificial intelligencein 6G. The 6G technologies, scenarios, and system architecture were also described [6].…”
Section: Related Workmentioning
confidence: 99%